2014
DOI: 10.1074/jbc.m114.581785
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Induces Direct Interaction of the p67 -Rac Complex with the Phagocyte Oxidase Nox2, Leading to Superoxide Production

Abstract: Background:The mechanism whereby arachidonic acid (AA) activates the phagocyte oxidase Nox2 is not well understood, except for the AA-induced conformational change of p47 phox , a partner of the Nox2 activator p67 phox . Results: AA also triggers Rac-GTP formation and Nox2 interaction with the p67 phox ⅐Rac-GTP complex. Conclusion: AA regulates Nox2 assembly at multiple steps. Significance: p67 phox -Nox2 interaction is a novel regulatory step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…Notably, neither inhibition of FLAP nor inhibition of prostaglandin synthesis by the COX-2 antagonist nimesulide blunted AA-induced ROS generation. This suggests that ROS may arise from the direct stimulation of NADPH oxidase by AA, as has been previously demonstrated for NOX1 in human colon adenocarcinoma cells [Sadok et al, 2008], NOX2 in HeLa cells [Matono et al, 2014], and NOX4 in human fibroblasts [Rossary et al, 2007]. Our data confirm the results of our previous studies showing that ROS, namely from NOX1 and NOX4, are critically involved in the regulation of vascular differentiation of murine ES cells [Sauer et al, 2005;Schmelter et al, 2006;.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Notably, neither inhibition of FLAP nor inhibition of prostaglandin synthesis by the COX-2 antagonist nimesulide blunted AA-induced ROS generation. This suggests that ROS may arise from the direct stimulation of NADPH oxidase by AA, as has been previously demonstrated for NOX1 in human colon adenocarcinoma cells [Sadok et al, 2008], NOX2 in HeLa cells [Matono et al, 2014], and NOX4 in human fibroblasts [Rossary et al, 2007]. Our data confirm the results of our previous studies showing that ROS, namely from NOX1 and NOX4, are critically involved in the regulation of vascular differentiation of murine ES cells [Sauer et al, 2005;Schmelter et al, 2006;.…”
supporting
confidence: 91%
“…Previous studies have indicated that AA induces ROS generation in cells [Chien et al, 2013] and cell-free systems [Souabni et al, 2012] via interaction of the p67(phox)-Rac complex with the phagocyte oxidase Nox2 [Matono et al, 2014]. Moreover, our studies have demonstrated that ROS are critically involved in vasculogenesis of ES cells [Sauer et al, 2005;Bekhite et al, 2010].…”
Section: Ros Generation In Embryoid Bodies Upon Aa Treatmentsupporting
confidence: 70%
See 1 more Smart Citation
“…Other studies on cPLA2 knockout mice suggested this phospholipase had no role in Nox2 activation [56], consistent with the dependence of murine Nox2 on the phospholipase A2 activity of Prdx6. Arachidonate and other soluble amphiphiles activate cell-free reconstitution of Nox2 and may act in promoting assembly and activation of Nox2 in whole cells by inducing structural changes in p47 phox and p67 phox that enable their interaction with membrane oxidase components, p22 phox and Nox2, respectively [57] [58]. Arachidonate or sodium dodecyl sulfate can also induce changes in Noxo1 that promote its interaction with p22 phox [14] [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, a careful study of the cPLA 2 null mouse demonstrated that this enzyme has minimal effect on activation of NOX2 in response to agonists [141]. Further, the role of arachidonate in NOX2 activation proved to be primarily an in vitro phenomenon, although arachidonic acid (as well as other unsaturated fatty acids) may bind to components of the NOX2 complex in vivo to stabilize their expression [142]. Subsequent attention focused on lysophospholipid as the product of PLA 2 activity that is required for NOX2 activation.…”
Section: Physiological Roles Of Prdx6mentioning
confidence: 99%